Embryonic Development of Yellow Prawn-Goby, Cryptocentrus cinctus (Herre, 1936) in the Hatchery - Oungern, Doungtip; Pichitkul, Phongchate; Wudtisin, Idsariya; Muthuwan, Vorathep (Burapha Science Journal, 2026)
An experiment was conducted to investigate the stage and period of embryonic of development in yellow prawn-goby Cryptocentrus cinctus (Herre, 1936) in the hatchery. An average standard length of broodstock was 4.21±0.32 (±SD) cm. average total length was 5.14±0.39 cm. and average weight was 1.44±0.22 gram (n =10, male 5: female 5) It was found that eggs were adhesive demersal eggs (the spawned eggs adhesive to substratum with adhesive egg membrane or filaments). Eggs average length was 1.66±0.02 mm. and average weight was 0.55±0 (n=10). Embryonic periods were 107 hrs. 33 min. after fertilization at water temperature 27-29 ๐c and salinity 33-35 ppt. The embryonic development is divided into 7 stages including 1. Zygotic 2. Cleavage 3. Blastula 4. Gastrula 5. Segmentation 6. Pharyngula and 7. Hatching out. An average standard length of hatched larvae was observed average standard length 2.28±0.03 mm. and the total length was 2.39±0.03 mm. (n=30)